Electronic Banking and Bank Performance: Botswana Context - MAPHARING, Mogotsinyana; BASUHI, Elang (Journal of Accounting, Business and Finance Research, 2017)
Electronic banking has redefined banking operations in many countries around the world. This paper investigates the relationship between e-banking and commercial bank performance in Botswana. Specifically, this was a descriptive study which seeks to find out if specific electronic banking indicators such as use of Automated Teller Machines (ATMs), Cheque Clearance (CHQ), Electronic Funds Transfer (EFT), and Card & Electronic Funds Transfer at Point of sale (EFTPOS) have an effect on financial bank performance. A 10 year aggregate quarterly commercial bank data as provided by Bank of Botswana Financial Statistics Reports was used in this study. A multiple regression procedure was used to determine the significance of the relationship between the independent variables (electronic banking indicators) and the profitability measures of return on assets (ROA) and return on equity (ROE) as the dependent variables. The findings were that only CHQ was statistically significant at 0.05% level under both ROA and ROE models with p-values of 0.0002 and 0.0000 respectively. However, the predictive power of ROE was found to be higher than ROA using adjusted r-square and d-statistic. The other three remaining variables (EFT, ATMs and EFTPOS) were statistically insignificant (p >0.05). The results show that at an aggregate level commercial banks in Botswana widely use the traditional banking methods such as use of cheques. The results are expected to inform bank managers on the need to discover the optimal supply of electronic banking services such as EFT clearing, EFTPOS and ATM payment systems in order to improve bank performance. The study will further inform policy makers on the need to improve on Information and Communication Technology (ICT) in order to cater for optimal use of electronic banking service in Botswana.